Nasal vs. oral BREATHing WIn Strategies in healthy individuals during cardiorespiratory Exercise testing (BreathWISE). - Massimo Mapelli; Elisabetta Salvioni; Irene Mattavelli; Giulia Grilli; Gabriele Zerboni; Alessandro Nava; Nicolò Capra; Arianna Galotta; Matteo Biroli; Gaia Bellini; Mattia Dall'Asta; Elisabetta Pasini; et al. (PLoS ONE, 2025)
Background Nasal and oral exclusive breathing modes have benefits and drawbacks during submaximal exercise. It is less known whether these responses would extend to anaerobic work performed at high intensity. The purpose of this study is to find the most efficient mode of breathing during different phases of a maximal exercise at cardiopulmonary exercise test (CPET). Methods Healthy subjects were recruited to perform 4 maximal CPETs (standard conditions (STD), exclusively nasal breathing (eNAS), exclusively oral breathing (eOR), partial nasal breathing (pNAS) with just one blocked nostril) using the same ramp protocol on an electronically braked cycle ergometer. Before the exercise a standard spirometry was executed in the same order. Twelve healthy subjects (28.6 ± 5.2 y, 50% males) performed the 4 CPETs within one month. Variables were analysed at rest, at anaerobic threshold (AT), at intermediate exercise steps, and at peak. Results Compared to STD, eOR, and pNAS conditions, eNAS was associated with a significant lower peakVO2, peakVCO2, peak ventilation, respiratory rate, VE/VCO2 slope, respiratory exchange ratio, and workload (p < 0.05 for all). Moreover, peak inspiration and peak expiration time were augmented, while forced expiratory volume and vital capacity at rest were reduced. Only minor differences were detected at rest or AT. eNAS breathing Borg scale was higher in all phases of the exercise. Conclusions In young healthy subjects, an exclusively nasal respiration induces significant impairment on peak exercise capacity at CPET due to ventilatory limitation, with only minor effects on metabolic parameters at rest and in submaximal effort.